THE SPECTRUM OF PULMONARY SARCOIDOSIS PRESENTED ON HRCT-WHAT RADIOLOGIST SHOULD KNOW?- REVIEW ARTICLE - Dimitrijevikj, Kristina (Journal of Morphological Sciences; Vol 8 No 1 (2025): JMS, 2025)
Sarcoidosis is a multisystem disease of unknown etiology that very often affects the lung parenchyma with interstitial and granulomatous changes of varying intensity and expression depending on the stage of the disease. Very often mediastinal lymph nodes are affected with changes of different types. It is also called the “great mimicker”, because of the various aspects of this enigmatic disease. In this review we will present typical and atypical variants of pulmonary sarcoidosis according to their distribution detected on HRCT from our experience. HRCT is the method of choice in the evaluation of pathological changes in pulmonary sarcoidosis. Its capabilities for thin-section imaging and high spatial reconstruction to generate quality images results in better characterization and determination of abnormalities of the lung parenchyma and interstitium. Key words: sarcoidosis, HRCT, lung, interstitial lung disease.